СОВРЕМЕННЫЕ НАЗВАНИЯ МОСКОВСКИХ АГЕНТСТВ НЕДВИЖИМОСТИ - ХРЫНКЕВИЧ-АДАМСКИХ, ВОЖЕНА (Studia Rossica Posnaniensia, 2006)
The change of the political and economic systems in Russia in 1992 caused a huge increase in the number of new commercial enterprises. The article is concerned with the presentday Russian ergonyms. First of all, the attempt at classification of the proper names of Moscow realty services is taken. The most important aspects of the analysis, that may later serve also for comparative purposes, are structural and connotative ones. What follows is an analysis of new phenomena in the area of ergonyms derived from foreign languages in contemporary Russian.